Infiltrating angiolipoma of the lower lip: A case report and literature review - OHNISHI, YUICHI (Oncol Lett, 2015)
Infiltrating angiolipoma (IAL) is a rare lesion and is a clinicopathological variant of angiolipoma. IAL occurs most commonly in the trunk and extremities, it is rarely found in the head and neck regions and extremely rare in the oral cavity. This study presents the case of a 74-year-old female with IAL of the lower lip. To the best of our knowledge, this is the first case of IAL arising in the lower lip to be reported. Microscopically, IAL was unencapsulated and mature lipocytes were separated by a branching network of proliferating small vessels that infiltrated the adjacent tissues. Therefore, complete excision was difficult to perform. Magnetic resonance imaging has been reported to be valuable in determining the extent of the tumor and asserting a preoperative diagnosis. According to previous studies, the recurrence rate of IAL following surgical extirpation is 35–50%. Furthermore, the levels of mRNA expression of the vascular endothelial growth factor (VEGF) family members in the tumor were investigated. VEGF-A and -B expression were detected, however, VEGF-C and -D were expressed at extremely low levels. Excisional biopsy was performed under local anesthesia. During four years of follow-up, no evidence of tumor recurrence had been identified. An operating microscope may be utilized for the total removal of an IAL to minimize damage to normal tissues. This report indicates that mast cell-derived VEGF may be responsible for the enhanced vascularity in the tumor. We would therefore consider careful extirpation with no wide safety margin to be the procedure of choice, except when the tumor invades irregularly into the muscles.